Kuroshio Intrusion and Its Impact on Swordtip Squid (Uroteuthis edulis) Abundance in the Southern East China Sea - Cheng, Yi-Chen; Jan, Sen; Chen, Chung-Chi (Frontiers in Marine Science, 2022)
Swordtip squid (Uroteuthis edulis) is a primary target species of the commercial fishery in the southern East China Sea (ECS), and they normally migrate to a quasi-permanent upwelling zone (called a cold dome) off northeastern Taiwan for spawning and growth during spring (March–May) and fall (October–December) in a year. We examined the connection of the variability in its standardized annual catch per unit effort (CPUE) during 2009–2017 in regard to the physical processes on the southern shelf of the ECS using temperature and wind observations from an isle north of Taiwan (Peng-jia-yu) as well as satellite sea surface temperature and absolute geostrophic velocity. The annual CPUE is positively correlated with the daily temperature anomaly at Peng-jia-yu in the cold dome in October of the previous year and April of the year. A warmer environment favors the recruitment and consequently the catch of the swordtip squid. During the spawning periods of the 9 years, the warm water carried by the Kuroshio frequently intruded atop the cold dome, which benefited the growth of the larvae and consequently helped maintain a certain value of the standardized annual CPUE. The anomalously low CPUE in 2012 and 2016 is attributed to the blocking of the Kuroshio intrusion due to cold and less salty China Coastal Water atop the cold dome in the spring spawning of 2012 and 2016. Based on the velocity strength in the cold dome and in a specified shelf region together with the daily temperature anomaly at Peng-jia-yu, an occupation intensity factor is used to evaluate the dominance of warm Kuroshio water and cold shelf water in the cold dome, which could help predict annual catches.